Ut pictura poesis in konsi. Pesem kot slika, pesem kot prostor - nesporazumi - Vrečko, Janez (Ars et humanitas, 2011)
One could hardly agree that Kosovel's konses anticipate visual poetry; that is, that they should serve as an obvious example of avantgarde poetry that synthesizes the semantic and visual dimension. Kosovel's konses belong to constructivism. The apex of the constructivist's scale of values is occupied by architecture, which is considered a synthesis of artistic, social, and technical practice and as such is also capable of reconstructing the world more rapidly than any other artistic current. In this synthesis, the limits between "spatial" arts such as architecture or sculpture and "temporal" arts such as music, dance, and poetry, as well as the limits between spiritual disciplines and technical engineering, disappear. There was no longer any chance of speaking about either Horace's syntagm ut pictura poesis or Lessing's theorem developed in his essay Laocoön: An Essay on the Limits of Painting and Poetry. Kosovel magnificently summarized this avantgarde tendency in Kons Z, and he recognized the synthesis of culture, politics, and arts in the domain of "new architecture for a man," binding it with "a man with a red shirt". Kons Sivo (Grey) articulates the basic tension of constructivism; that is, the dynamization and kinetization of poetry, and this is why the artist must act "with a sounding line in his hand, with eyes as precise as a ruler, with the soul as stretched as compasses" (Rodchenko). In this kons, sketches and letters also broke through the plane, growing into the space without losing their semantic dominating feature.
Keywords: Kosovel, Srečko, 1904-1926; Slovene poetry; slovenska književnost; literary avant-garde; Slovene literature; constructivism; slovenska poezija; visual poetry; literarna avantgarda; konstruktivizem; konsi; vizualno pesništvo; literarne študije; kons